Straining Psychic and Social Sinew: Trauma among Adolescent Psychiatric Patients in New Mexico. (19th June 2014) - Jenkins, Janis H.
Abstract : Drawing on data from a longitudinal study of 47 adolescents of diverse ethnic backgrounds hospitalized for psychiatric disorder in New Mexico, the article critically examines the relevance of post‐traumatic stress disorder (PTSD) to address anthropological questions of how to define the problem. Factors include the utility/limitation of psychiatric diagnostic categories, the lived experience of severe distress, the socioeconomic and political conditions of suffering, and reciprocal relations between immediate and remote social institutions. I discuss the mental health care system for adolescents and present two case studies of young inpatients, emphasizing the need for dual specification of the conditions of trauma and the structure of experience. I argue for understanding patterns of abandonment that shape the raw existence of young people at both the personal and collective levels to apprehend their depth and durability.